Humoral and cellular immune response to SARS-CoV-2 mRNA BNT162b2 vaccine in pediatric kidney transplant recipients compared with dialysis patients and healthy children - YILDIZ, NURDAN (My University, 2022)
Background Compared with the general population, the immune response to COVID-19 mRNA vaccines is lower in adult kidney transplant recipients (KTRs). However, data is limited for pediatric KTRs. In this study, we aimed to assess humoral and cellular immune responses to the COVID-19 mRNA vaccine in pediatric KTRs. Methods This multicenter, prospective, case–control study included 63 KTRs (37 male, aged 12–21 years), 19 dialysis patients, and 19 controls. Humoral (anti-SARS-CoV2 IgG, neutralizing Ab (nAb)) and cellular (interferon-gamma release assay (IGRA)) immune responses were assessed at least one month after two doses of BNT162b2 mRNA vaccine. Results Among COVID-19 naïve KTRs (n=46), 76.1% tested positive for anti-SARS-CoV-2 IgG, 54.3% for nAb, and 63% for IGRA. Serum levels of anti-SARS-CoV-2 IgG and nAb activity were signifcantly lower in KTRs compared to dialysis and control groups (p<0.05 for all). Seropositivity in KTRs was independently associated with shorter transplant duration (p=0.005), and higher eGFR (p=0.007). IGRA titer was signifcantly lower than dialysis patients (p=0.009). Twenty (43.4%) KTRs were positive for all immune parameters. Only four of 11 seronegative KTRs were IGRA-positive. COVID19 recovered KTRs had signifcantly higher anti-SARS-CoV-2 IgG and nAb activity levels than COVID-19 naïve KTRs (p=0.018 and p=0.007, respectively). Conclusions The humoral and cellular immune responses to SARS-CoV-2 mRNA BNT162b2 vaccine are lower in pediatric KTRs compared to dialysis patients. Further prospective studies are required to demonstrate the clinical efcacy of the mRNA vaccine in KTRs. This prospective study was registered in ClinicalTrials.gov (NCT05465863, registered retrospectively at 20.07.2022).
Keywords: mRNA vaccine; BNT162b2; COVID-19; Immune response; Anti-SARS-CoV-2 IgG; IGRA; Neutralizing antibody